A Case of Advanced Descending Colon Cancer in an Adult Patient with Intestinal Malrotation. (3rd March 2016) - Nakayama, Yoshifumi; Akiyama, Masaki; Sawatsubashi, Yusuke; Minagawa, Noritaka; Torigoe, Takayuki; Hirata, Keiji
Abstract : This report presents an operative case of advanced descending colon cancer in an adult patient with intestinal malrotation. A 63-year-old Japanese male was suffering from left side abdominal pain, abdominal distension, and constipation. An endoscopic examination revealed an advanced tumor in the descending colon. Computed tomography (CT) of the abdomen revealed the thickening of the descending colon wall and superior mesenteric vein rotation. An opaque enema detected severe stenosis of the descending colon. An abdominal X-ray examination revealed the dilation of the colon and small intestine with niveau. At the insertion of an ileus tube, the C-loop of the duodenum was observed to be absent and the small intestine was located on the right side of the abdomen. After the decompression of the bowel contents, laparotomy was performed. Descending colon cancer was observed to have directly invaded the left side of the transverse colon. Left hemicolectomy, lymph node dissection, and appendectomy were performed. The patient had an uneventful recovery and was discharged from the hospital on the 16th day after surgery. This report presents a rare operative case of descending colon cancer in an adult patient with intestinal malrotation.